Influence of three lighting regimes during ten weeks growth phase on laying performance, plasma levels- and tissue specific gene expression- of reproductive hormones in Pengxian yellow pullets. - Shunshun Han (PLoS ONE, 2017)
The study was conducted to optimize lighting schedule for pre-pubertal (12 to 22 weeks) Chinese native breed Pengxian yellow pullet. A total of 414 healthy pullets (10 weeks), with similar body weight were randomly distributed into three groups (n = 138) and housed in individual cages for up to 12 weeks of age in light controlled rooms and provided normal lighting schedule (10L:14D). At 12 to 18 weeks of age, pullets were housed in three rooms, having varying lighting schedule viz. G1 (8L: 16D), G2 (10L:14D), or G3 (12L:12D). From 19th week onwards lighting schedule was gradually increased every week in incremental manner till all groups started receiving 16L:8D lighting schedule. The age at first egg, weight of first egg laid, percent peak hen day egg production, concentration of plasma luteinizing and follicle-stimulating hormones and expression of genes regulating synthesis or/and secretion of hypothalamic gonadotropin-releasing hormone-I (GnRH-I), and pituitary LH-β and FSH-β were studied during experimental period (12 to 43 weeks of age) of this study. The result indicated that pullets of long day length (G3) group had higher plasma levels of FSH and LH and also better mRNA expression that regulates synthesis or/and secretion of GnRH-I, FSH-β, and LH-β before egg laying. The age at first egg (151.3 days) in pullets of G3 group receiving longer lighting hours (12L:12D) was 8.8 days less (P<0.05) compared to pullets of G1 group, while it was 6.9 days less (P>0.05) compared to G2. However, significantly higher (P<0.05) plasma levels of LH and FSH in pullets of G1 as compared to pullets belonging to G3 group corresponded with the higher (P<0.05) cumulative egg production during the experimental period, while these attributes in G2 group didn't differ from either G1 or G3 groups. Pullets of G1 group had significantly higher levels (P<0.05) of GnRH-I, FSH-β, and LH-β mRNA abundances at 43 weeks of age than other two groups and this corresponded with the percent (hen day) peak egg production (75.38%) in pullets in this G1 group that was attained at 32 weeks of age, while the peak production of 71.24% was attained at 30 weeks of age in G3 group. There was no effect of lighting schedule on body weight of pullets, recorded during experimental period, at all occasions; belonging to three groups (G1,G2 and G3) and receiving varying hours of photo-stimulation (P>0.05). It was inferred that the optimum lighting schedule for Chinese native breed Pengxian yellow pullets during 10 weeks of pre-pubertal growth period is short hours of photo-stimulation (i.e 8L:16D).